Use of intramyometrial carbetocin in caesarean myomectomy to reduce hemorrhage - Yaliwal, Rajasri G.; Lakshmi, Shilpa; Biradar, Aruna M.; Sangolli, Laxmi S.; Bankapur, Gauri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Traditionally myomectomy is avoided during caesarean delivery because of potential excessive blood loss. As the size increases, blood supply of leiomyomas also increases in pregnancy, and specifically at term due to the effect of human chorionic gonadotropin. Carbetocin is an oxytocin analog. It is long acting and is effective in preventing blood loss. It has been used in myomectomy to prevent blood loss in non-pregnant uterus. We present a case report where it is used intramyometrial route during caesarean section. A 30-year-old multigravida of 38 weeks period of gestation with previous caesarean section, presented in labor. Her recent ultra sound report showed single live intrauterine fetus of 35 weeks 3 days with a single posterior wall fibroid. The woman requested for myomectomy along with caesarean delivery as she had heavy menstrual bleeding caesarean section was done and myomectomy was planned along with the caesarean section. Intramyometrial carbetocin 100 mcg was used to prevent excessive blood loss. The patient had an uneventful post-operative period. Intramyometrial carbetocin is an effective method to reduce blood loss in myomectomy during caesarean delivery.